Spectral domain optical coherence tomography imaging in optic disk pit associated with outer retinal dehiscence - Wong CW (Dove Medical Press, 2014)
Chee Wai Wong,1,2 Doric Wong,1,2 Ranjana Mathur1,2 1Singapore National Eye Centre, Singapore; 2Singapore Eye Research Institute, Singapore Abstract: A 37-year-old Bangladeshi male presented with an inferotemporal optic disk pit and serous macular detachment in the left eye. Imaging with spectral domain optical coherence tomography (OCT) revealed a multilayer macular schisis pattern with a small subfoveal outer retinal dehiscence. This case illustrates a rare phenotype of optic disk maculopathy with macular schisis and a small outer retinal layer dehiscence. Spectral domain OCT was a useful adjunct in delineating the retinal layers in optic disk pit maculopathy, and revealed a small area of outer retinal layer dehiscence that could only have been detected on high-resolution OCT. Keywords: retinal imaging, maculopathy, macular schisis